Implementation and adaptation of the Re-Engineered Discharge (RED) in five California hospitals: a qualitative research study - S. E. Mitchell; G. M. Weigel; V. Laurens; J. Martin; B. W. Jack (BMC, 2017)
Abstract Background Project Re-Engineered Discharge (RED) is an evidence-based strategy to reduce readmissions disseminated and adapted by various health systems across the country. To date, little is known about how adapting Project RED from its original protocol impacts RED implementation and/or sustainability. The goal of this study was to identify and characterize contextual factors influencing how five California hospitals adapted and implemented RED and the subsequent impact on RED program sustainability. Methods Participant observation and key informant and focus group interviews with 64 individuals at five California hospitals implementing RED in 2012 and 2013 were conducted. These involved hospital leadership, personnel responsible for Project RED implementation, hospital staff, and clinicians. Interview transcripts were coded and analyzed using a modified grounded theory approach and constant comparative analysis. Results Both internal and external contextual factors were identified that influenced hospitals' decisions on RED adaptation and implementation. These also impacted RED sustainability. External factors included: impending federal penalties for hospitals with high readmission rates targeting specific diagnoses, and access to external funding and technical support to help hospitals implement RED. Internal or organizational level contextual factors included: committed leadership prioritizing Project RED; RED adaptations; depth, accountability and influence of the implementation team; sustainability planning; and hospital culture. Only three of the five hospitals continued Project RED beyond the implementation period. Conclusions The sustainability of RED in participating hospitals was only possible when hospitals approached RED implementation as a transformational process rather than a patient safety project, maintained a high level of fidelity to the RED protocol, and had leadership and an implementation team who embraced change and failure in the pursuit of better patient care and outcomes. Hospitals who were unsuccessful in implementing a sustainable RED process lacked all or most of these components in their approach.